NALURI PENGARANG DALAM NOVEL SOGI KARYA FAIKA BURHAN - Qadriani, Nur Lailatulul; Nurhadi, Sitti Aisyah (Seshiski: Southeast Journal of Language and Literary Studies, 2022)
The purpose of this research is to describe the form of the author's instinct revealed in the novel Sogi written by Faika Burhan. This study uses Sigmund Freud's psychoanalytic theory. This type of research is library research with descriptive qualitative method. The result of analysis showed that the author's instinct in the novel appeared through the form of the author's unconsciousness in his work. This unconsciousness is manifested through the depiction of events that occur regarding the behavioral decisions taken by the characters in Sogi novel. These behaviors are divided into two main topics, namely the life instinct and the death instinct. The life instincts found in Sogi novel are life instincts as basic needs and instincts as sexual needs. Meanwhile, the death instinct in Sogi novel is the death instinct towards oneself, the death instinct towards others (parents towards their children and children against their parents).